Physical activity and motor competence in childhood - Silva, Mellina Maria Lago Manso; Catuzzo, Maria Teresa; Monteiro, Carlos Bandeira Mello; Tudela, Mariana; Ré, Alessandro Hervaldo Nicolai (Journal of Physical Education (Maringá), 2019)
The objectives of this research were to verify the amount and intensity of physical activity performed by children of low socioeconomic level during weekdays and weekends, to assess motor competence indicators and to verify associations between these variables. A total of 176 children aged 3 to 6 years old participated in the study. They wore an accelerometer for seven consecutive days to measure physical activity engagement, while motor competence was measured by means of the Test of Gross Motor Development (TGMD-2). Boys spent more time on total physical activity than girls did (222.5 min x 204 min; p<0.01) on weekdays. For both sexes, daily average time of total physical activity stood above international guidelines on physical activity (≥ 3h of physical activity per day), but there are indicators of delayed motor competence development, especially in object control skills. In conclusion, boys presented higher physical activity engagement indexes compared to girls and had greater motor competence; however, low values for association between physical activity and motor competence suggest that physical activity amount does not necessarily affect motor competence development.